Implementasi Pengaruh Moderasi Beragama pada Masyarakat Karo, Desa Simacem, Kabupaten Karo, Sumatera Utara Kawasan Relokasi Siosar Puncak 2000 - Afrahul Fadhilah Daulay; Muhamad Basyr; Yulia Citra; Inda Lestari; Hazra Ria Habibah (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Religion and culture play a central role in building harmonious relationships between followers of different religions, both in the nuclear family and in the extended family. This study examines the revitalization of religious moderation with a cultural approach in strengthening tolerance. Data was obtained qualitatively from in-depth interviews and observations of families of different religions, religious leaders, traditional leaders and other related informants. The research results show that the family institution is the most crucial forum for carrying out moderate religious culturalization through local wisdom values ​​of kinship, kinship and togetherness. Institutionally, traditional leaders, religious leaders and the Batak tribe encourage peace in society, both in traditional and religious activities. Meanwhile, religious celebrations, traditional ceremonies and community activities are opportunities for socializing and interacting while promoting firm tolerance towards religious differences.